2022
DOI: 10.1186/s12935-022-02729-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pyroptosis-related genes and long non-coding RNAs signatures in osteosarcoma

Abstract: Osteosarcoma is a highly malignant tumor, with very high disability and fatality rates. However, the overall prognosis is not optimistic. Pyroptosis is a newly discovered cell death modality accompanied by inflammation, which is closely related to varieties of cancers. In this study, the RNA-seq data were downloaded from public databases, the differences in the expression of the pyroptosis-related genes (PRGs) were identified, and the six PRGs signature was established through the univariate and LASSO Cox anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…Additionally, the overexpression of CHMP4C notably enhanced the proliferation and migration of MG63 cells. Conversely, interference with CHMP4C yielded opposite effects, aligning with the observations reported by Zhang et al (2022). In addition, we validated the in vivo role of CHMP4C.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, the overexpression of CHMP4C notably enhanced the proliferation and migration of MG63 cells. Conversely, interference with CHMP4C yielded opposite effects, aligning with the observations reported by Zhang et al (2022). In addition, we validated the in vivo role of CHMP4C.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we conducted an analysis of CHMP4C and the related proteins GSK3β, p-GSK3β, and β-catenin. CHMP4C is a protein associated with the endocytic pathway and closely linked to processes such as cell division, endocytosis, and signal transduction ( Zhang et al, 2022 ). Research has indicated a significant association between the GSK3β/β-catenin signaling pathway and osteosarcoma proliferation ( Ruan and Zhao, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the AC090559.1 contributes to CASP1, GSDMA expression and thus promotes pyroptosis to inhibit osteosarcoma development. 87 In addition, microRNAs have also been associated with osteosarcoma cell pyroptosis. For example, miRNA‐181a can inhibit NLRP3‐dependent cellular pyroptosis, so low expression of miRNA‐181a contributes to the occurrence of cellular pyroptosis and thus suppresses tumor growth.…”
Section: Mechanisms Of Cell Death In Osteosarcomamentioning
confidence: 99%
“…For example, FOXD2‐AS1 is a proto‐oncogene, which can induce cancer. In addition, the AC090559.1 contributes to CASP1, GSDMA expression and thus promotes pyroptosis to inhibit osteosarcoma development 87 . In addition, microRNAs have also been associated with osteosarcoma cell pyroptosis.…”
Section: Mechanisms Of Cell Death In Osteosarcomamentioning
confidence: 99%
“…Additionally, the role of pyroptosis in osteosarcoma development, although not fully understood, is becoming increasingly recognized, emphasizing the need for further research in this area. 9,10 Pyroptosis is mediated by gasdermin (GSDM) proteins, triggering immune cell activation and infiltration. [11][12][13] The expression of GSDMD, in particular, is essential for the anti-tumour function of CD8 + T cells, 14 and GSDME may act as a tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%